The appearance of the discretionary prosecution principle in Spanish criminal proceedings - Vecina Cifuentes, Javier (2018)
Proceduralist doctrine has been debating intensively the principle of legality/discretionary prosecution principle dichotomy, without the necessary consensus about this extreme having yet been achieved to date. In Spain, the controversy still focuses on the convenience or not of incorporating now into the system the most relevant manifestations of the centennial Law of Criminal Procedure despite the successive reforms of this norm that have been introducing manifestations of the discretionary prosecution principle. Thus, this article seeks to determine if a criminal process must be informed by the discretionary prosecution principle, and to what extent it must be, constitutes, in short, an option of legislative policy that must be exercised taking into account the Constitution of each country and the role that is attributed to criminal law and criminal procedure law.